Evaluation of the Properties of PHB Composite Filled with Kaolin Particles for 3D Printing Applications Using the Design of Experiment - Menčík, Přemysl; Přikryl, Radek; Krobot, Štěpán; Melčová, Veronika; Kontárová, Soňa; Plavec, Roderik; Bočkaj, Jan; Horváth, Vojtech; Alexy, Pavol (International journal of molecular sciences, 2022)
In the presented work, poly(3-hydroxybutyrate)-PHB-based composites for 3D printing as bio-sourced and biodegradable alternatives to synthetic plastics are characterized. The PHB matrix was modified by polylactide (PLA) and plasticized by tributyl citrate. Kaolin particles were used as a filler. The mathematical method "Design of Experiment" (DoE) was used to create a matrix of samples for further evaluation. Firstly, the optimal printing temperature of the first and upper layers was determined. Secondly, the 3D printed samples were tested with regards to the warping during the 3D printing. Testing specimens were prepared using the determined optimal printing conditions to measure the tensile properties, impact strength, and heat deflection temperature (HDT) of the samples. The results describe the effect of adding individual components (PHB, PLA, plasticizer, and filler) in the prepared composite sample on the resulting material properties. Two composite samples were prepared based on the theoretical results of DoE (one with the maximum printability and one with the maximum HDT) to compare them with the real data measured. The tests of these two composite samples showed 25% lower warping and 8.9% higher HDT than was expected by the theory.
Keywords: pomocné látky; FDM; 3D tisk; Printing, Three-Dimensional; Design of Experiment; Kaolin; composite; polyestery; kaolin; Excipients; Polyesters; PHB; vysoká teplota; 3D printing; Hot Temperature